Unveiling the Impact of Strategic Sensitivity and Strategic Response on SME Performance Amidst COVID-19: Examining the Mediating Role of Innovation Capacity - Sajuyigbe, Ademola Samuel; Ladokun, Isaac Olujide; Obi, Nwoye James; Oladeji, Alaba Adesola; Adeyemi, Mariam Adebisi (Journal of Technology Management and Business, 2024)
Scholars have highlighted the pivotal role that Small and Medium Enterprises (SMEs) play in fostering economic sustainable development across nations. However, the SME sector has been significantly challenged by the repercussions of the COVID-19 pandemic and shifts in the global competitive landscape, resulting in decreased profits. This study explores the mediating role of innovation capacity in the relationship between strategic sensitivity, strategic response, and the performance of SMEs. Data were collected using a structured questionnaire from 405 participants and analyzed using Path Analysis - Structured Equation Modeling (PA-SEM). The findings confirm that strategic sensitivity significantly and positively affects SME performance and innovation capacity. Similarly, strategic response shows a positive and significant correlation with SME performance. Among the studied variables, innovation capacity has the most robust positive impact on SME performance. The research also indicates that innovation capacity serves as a partial mediator in the relationships between strategic sensitivity and SME performance, as well as between strategic response and SME performance. This implies that the beneficial effects of strategic sensitivity and strategic response on SME performance are partly due to their impact on innovation capacity. The study recommends that SMEs invest in research and development, foster creativity, and adopt new technologies as crucial strategies for achieving long-term success.